Potential pharmacotherapy pathways in metabolic dysfunction-associated steatotic liver disease - Rajewski, Paweł; Cieściński, Jakub; Rajewski, Piotr; Suwała, Szymon; Rajewska, Alicja; Potasz, Maciej (Clinical and Experimental Hepatology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common chronic liver disease worldwide, one of the leading causes of cirrhosis, hepatocellular carcinoma and liver transplantation in developed countries, and an important cardiovascular risk factor. It affects about 30% of the adult population and about 10% of the paediatric population. These figures may be underestimated due to the long-standing asymptomatic or oligosymptomatic course of the disease, the lack of nationwide screening for MASLD in patients with risk factors for its development, and the low awareness of both patients and physicians themselves. According to projections, this number could double by 2030 due to the growing obesity epidemic and the associated development of other weight-dependent metabolic complications, such as insulin resistance, pre-diabetic state, type 2 diabetes, lipid disorders and hypertension. The basis for prevention and treatment of MASLD is weight reduction with diet and regular physical activity and modern pharmacotherapy for obesity-related disease, as well as treatment aimed at reducing the cardiometabolic factors – diabetes, hyperlipidaemia and hypertension. Pharmacological treatment of hepatic steatosis, steatohepatitis or liver fibrosis alone is limited, and many drugs are currently in clinical trials. This article presents the current pharmacological options and potential pharmacotherapy pathways for the hepatic complications of MASLD – steatosis, steatohepatitis and incipient liver fibrosis.